P03.14 High prevalence of lactobacillis crispatus among adolescent girls attending secondary school in tanzania. (13th September 2015) - Francis, SC; Jespers, V; Hansen, C; Irani, J; Baisley, K; Andreasen, A; Nnko, S; Crucitti, T; Changalucha, C; Hayes, RJ; Watson-Jones, D; Buve, A
Abstract : Introduction: Prevalence and incidence of HIV infection and other sexually transmitted infections (STIs) are particularly high among adolescent girls in sub-Saharan Africa. The role played by the vaginal microbiota in susceptibility to HIV and other STIs in adolescent girls is unclear. The aim of this study was to characterise the vaginal microbiota of adolescent girls in Tanzania around the time of their sexual debut. Methods: Girls aged 17–18 years old attending secondary schools in Mwanza City were invited to join a cross-sectional study. After informed consent/assent, girls were interviewed and vaginal swabs were obtained and tested for the following species by in-house quantitative PCR: Lactobacillus crispatus, L. iners, L. gasseri, L. jensenii, L. vaginalis, Atopobium vaginae, and Gardnerella vaginalis . Differences in the prevalence of bacterial species were analysed using logistic regression. Results: Of the 403 girls enrolled, 385 provided samples for this analysis. Of these, 163 reported having had sexual intercourse. Prevalences of bacterial species were as follows (overall; sexually active/sexually naïve): L. crispatus (69%; 60%/75%), L. iners (83%; 85%/80%), L. gasseri (22%; 21%/23%), L. jensenii (49%; 40%/55%), L. vaginalis (66%; 55%/74%), A. vaginae (44%; 56%/34%), and G. vaginalis (62%; 75%/52%). Prevalences of A. vaginae and G. vaginalis were higher among girls who reported sexual intercourse (OR: 2.5; 95% CI: 1.7–3.8 and OR: 2.8; 95% CI: 1.8–4.4, respectively), while prevalences of L. crispatus, L. jensenii, and L. vaginalis were lower in sexually active girls (OR: 0.5; 95% CI: 0.3–0.8, OR: 0.5; 95% CI: 0.4–0.8, and OR: 0.4; 95% CI: 0.3–0.6, respectively). Conclusion: Among girls attending secondary school in Tanzania, sexual debut was associated with quantifiable changes in vaginal microbiota. BV-associated bacteria were present in many girls before reported sexual debut. Additionally, the prevalence of L. crispatus was higher than expected; a recent study showed the prevalence among African women to be relatively low (17–38%). This challenges the view that women in sub-Saharan Africa have less L. crispatus colonisation. Disclosure of interest statement: The authors do not have a conflict of interest. No pharmaceutical grants were received in the development of this study.